1995
DOI: 10.1074/jbc.270.10.5213
|View full text |Cite
|
Sign up to set email alerts
|

CD14: Physical Properties and Identification of an Exposed Site That Is Protected by Lipopolysaccharide

Abstract: Soluble CD14 (sCD14) is a 55-kDa serum protein that binds lipopolysaccharide (LPS) and mediates LPS-dependent responses in a variety of cells. Using recombinant sCD14 expressed in Chinese hamster ovary (CHO) cells, we examined the structural characteristics of sCD14 and sCD14.LPS complexes. The circular dichroism and fluorescence spectra of the sCD14 indicate that it contains substantial beta-sheet (40%) and a well-defined tertiary structure with the tryptophan residues located in environments with different d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 13 publications
3
49
0
2
Order By: Relevance
“…This is confirmed by a recent X-ray structure of mouse sCD14 which depicts a α/β fold for the protein [16]. The spectrum of sCD14-EBD changes minimally upon addition of the endotoxin ligand ReLPS, suggesting there are no global conformational changes in the protein upon ligand binding [22]. Similar results were obtained upon binding of other ligands such as LTA and MDP (data not shown).…”
Section: Expression and Isotopic Labeling Of Scd14 In Pichia Pastorissupporting
confidence: 76%
“…This is confirmed by a recent X-ray structure of mouse sCD14 which depicts a α/β fold for the protein [16]. The spectrum of sCD14-EBD changes minimally upon addition of the endotoxin ligand ReLPS, suggesting there are no global conformational changes in the protein upon ligand binding [22]. Similar results were obtained upon binding of other ligands such as LTA and MDP (data not shown).…”
Section: Expression and Isotopic Labeling Of Scd14 In Pichia Pastorissupporting
confidence: 76%
“…1) were independently necessary for LPS ligand binding. Subsequently, protease protection experiments, an additional deletion CD14 mutation protein, and mAb epitope mapping identified region 4 as required for E. coli LPS binding (14,15). Another study confirmed that region 3 is involved in E. coli LPS binding with the use of multiple alanine replacement mutations and monoclonal epitope mapping (16).…”
mentioning
confidence: 58%
“…A major portion of the 6C8 epitope is located in the hydrophilic region 4 (residues R53 to D59; see Table II). This region of CD14 has been identified as an E. coli LPS binding site based upon mutational analysis (15), mAb binding (15), and protease protection experiments (14). Residue D59 is probably a contact residue for Ab 6C8.…”
Section: Discussionmentioning
confidence: 99%
“…Region 4 includes residues from the loop connecting ␣2 and ␣3 helices. This area is labile to proteolysis in the absence of bound LPS but becomes resistant when LPS is bound (31). Furthermore, the antibodies MEM18, CRIS-6, and 6C8 that block LPS binding bind to the same region (23)(24)(25).…”
Section: Structure Determination and Overall Structure Of Cd14 -mentioning
confidence: 99%